Physical activity recommendations during the COVID-19 virus outbreak - Jurak, G.; Morrison, S. A.; Leskošek, B.; Kovac, M.; Hadžic, V.; Vodicar, J.; Truden, P.; Starc, G. (Childhood obesity, 2020)
Physical activity significantly reduces the risk of viral infections and levels of anxiety. In addition to its short-term benefits, regular physical activity lowers one`s risk of suffering from chronic health conditions (e.g.diabetes, coronary heart disease, hypertension) which are cited as the most frequent comorbidities in recent studies of COVID-19. Because of the COVID-19 pandemic that has become a global problem, many will face the necessity of requiring hundreds of millions of people to volitionally self-confine themselves in their own homes, or even be` locked down` in a quarantined community. Confinement affects most aspects of human physiology considerably. It can be induced operationally (submarines, polarstations, and deep-sea laboratories), during expeditions (e.g. Antarctica over-wintering) and, as many are now experiencing, for population health and global security reasons. The psychological stress of remaining in a confined space causes endocrinological changes tha tinturn, affect immunestatus and have other negative psychological effects including post-traumatic stress symptoms, confusion, an danger.